2005
DOI: 10.1152/ajpregu.00537.2004
|View full text |Cite
|
Sign up to set email alerts
|

NK1 receptor activation in rat rostral ventrolateral medulla selectively attenuates somato-sympathetic reflex while antagonism attenuates sympathetic chemoreflex

Abstract: The effects of activation and blockade of the neurokinin 1 (NK1) receptor in the rostral ventrolateral medulla (RVLM) on arterial blood pressure (ABP), splanchnic sympathetic nerve activity (sSNA), phrenic nerve activity, the somato-sympathetic reflex, baroreflex, and chemoreflex were studied in urethane-anesthetized and artificially ventilated Sprague-Dawley rats. Bilateral microinjection of either the stable substance P analog (pGlu5, MePhe8, Sar9)SP(5-11) (DiMe-SP) or the highly selective NK1 agonist [Sar9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…3). 4) NK1 receptors that bind SP are found in the RVM (Makeham et al, 2005), but whether these receptors co-localize with serotonin containing neurons is inconclusive. 5) Glutamate neurons that inhibit nociceptive responses exist in the RVM (Winkler et al, 2006), as do SP-ir neurons (Menetrey and Basbaum, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 4) NK1 receptors that bind SP are found in the RVM (Makeham et al, 2005), but whether these receptors co-localize with serotonin containing neurons is inconclusive. 5) Glutamate neurons that inhibit nociceptive responses exist in the RVM (Winkler et al, 2006), as do SP-ir neurons (Menetrey and Basbaum, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…al‥, 1978), but the connection has not been shown directly. Lastly, NK1 receptors that bind SP are found in the RVM (Makeham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(e) Other peptides As noted earlier, many other peptides play an important role in the tonic and reflex regulation of the cardiorespiratory systems, including substance P (Gilbey et al 1983;Makeham et al 2001Makeham et al , 2005, pituitary adenylate cyclase-activating polypeptide (PACAP; Farnham et al 2008), somatostatin (Burke et al 2008), galanin (Stornetta et al 2009;figure 2b), which is present in many chemosensitive neurons in the retrotrapezoid nucleus, and thyrotropin-releasing hormone (Murphy et al 1995;Sun et al 1995Sun et al , 1996. The effects of these neuromodulators are site specific and in most cases their physiology is still very poorly understood.…”
Section: Peptides In Cardiorespiratory Regulationmentioning
confidence: 98%
“…Although NK1-R are localized throughout the VRG (Gray et al 1999;Guyenet et al 2002;Nakaya et al 1994;Wang et al 2001) with expression confirmed on preinspiratory neurons , the effect of direct activation of NK1-R expressing expiratory neurons on respiratory rhythm has not been thoroughly explored. Although substance P can decrease respiratory frequency by prolonging expiratory duration (Chen et al 1990b;Fong and Potts 2006;Makeham et al 2005), the functional expression of NK1-R on individual expiratory neurons has not been demonstrated. We now provide evidence that exogenous SP modulates the excitability of a subpopulation of E neurons suggesting a possible functional role for NK1-Rs in an expiratory region of the VRG.…”
Section: Substance P Modulates the Excitability Of Expiratory Neuronsmentioning
confidence: 99%